Rekonstruksi Konsep Kesetaraan Gender dalam Al-Qur’an: Analisis Tafsir Maudhu’i dan Implikasinya Terhadap Pendidikan Islam Kontemporer - Rizka Aulia; Assya Syahnaz (Journal of Innovative and Creativity, 2026)
Gender equality remains one of the most contested issues in contemporary Muslim societies, particularly when religious texts are positioned as sources of legitimacy for unequal gender relations. Misinterpretative and patriarchal readings of the Qur’an have often contributed to the marginalization of women, especially in educational and socio-cultural contexts. This article aims to reconstruct the concept of gender equality in the Qur’an through a thematic (tafsir maudhu‘i) analysis and to examine its implications for contemporary Islamic education. This study employs a qualitative library research method by analyzing Qur’anic verses related to human creation, servanthood, leadership, moral responsibility, and social roles, supported by classical and contemporary Qur’anic exegesis as well as gender studies literature. The findings indicate that the Qur’an consistently affirms the ontological and moral equality of men and women as servants of God and vicegerents on earth. Biological differences are not intended to establish hierarchical relations but rather functional complementarity. Consequently, integrating Qur’anic-based gender equality into Islamic education is essential for fostering justice, inclusivity, and human dignity in Muslim societies.